The method for providing quality of service time requirements in reconfigurable computing systems - Klymenko, Iryna; Kulakov, Yurii; Tkachenko, Valentyna; Storozhuk, Oleksandr (Eastern-European Journal of Enterprise Technologies, 2016)
The process of calculations control in reconfigurable computing systems characterized by the time constraints of both the applications solved and the functional and structural organization of the system is investigated. As part of this, the method is modified and mathematically substantiated for determining the time intervals of tasks. The proposed modification to the analysis of tasks acceleration index allows to evaluate the unproductive time expenditure taking into account the FPGA hardware limitations in the computer algorithms mapping to the reconfigurable computing structure. The method of providing time parameters of service quality in the reconfigurable computing system that provides given application runtime by determining the amount of unproductive time-consuming reconfiguration and the choice of optimal service discipline for each task in terms of time and existing hardware limitations was proposed. The use of the proposed method of determining the time intervals, which the implementation of the method is based on determining the sequence of tasks for which the target architecture of the computer system is effective and the use of additional mechanisms to reduce overhead does not speed up calculations within the advertised time requirements. Application of the proposed method allows to determine and optimize the impact of space limitations the reconfiguration time and reduce the number of rejections of tasks in the dynamic mapping of task flows to the reconfigurable computational structure. The formalization of the method for determining the time intervals of tasks was developed, for which the optimal boundaries of the effective use of the proposed facilities in terms of the adequacy of the offered application time limits to the limits of the reconfigurable computer system were defined and justified. The proposed tools can be used in modern high-performance reconfigurable computing systems during solving the problems of control of various technical and management processes and implementation of multidimensional calculations in complex information systems.